The Role of Supply Chain Flexibility and Agility in Improving SMEs’ Performance - Baziedy Aditya Darmawan; Firman Agum Gunawan; Siti Nursyamsiah; Nur Rahmah Tri Utami (Journal of Business and Management Review, 2023)
The supply chain has a vital role in maintaining a competitive advantage. Although there have been many studies on supply chains, research on supply chains involving SMEs is still limited. The aim of this study is to determine how the performance of SMEs is impacted by supply chain agility and supply chain flexibility. A convenience sampling technique was applied in this study to choose 125 samples of SMEs from the Sleman Regency, Yogyakarta, Indonesia. The hierarchical regression test used in this study revealed that SCF positively affects SCA and SMEs’ performance. In addition, research also found that SCA is an essential predictor of SMEs’ performance. Furthermore, this study proves that SCA is a variable that mediates the effect of SCF on SMEs’ performance. The results of this study support several previous studies related to the relationship between SCF and SCA on company performance. This study provides empirical evidence that can be used to encourage SMEs’ performance improvement through the implementation of SCF and SCA.